Translation, validation, and cultural adaptation of the Rhinosinusitis Disability Index and the Chronic Sinusitis Survey into Arabic - Aldrees, Turki (Ann Saudi Med, 2018)
BACKGROUND: Disease-specific quality of life instruments assess the impact of chronic rhinosinusitis on patients’ quality of life (QoL). To the extent of our knowledge, there are no Arabic versions of two instruments—the Rhinosinusitis Disability Index (RSDI) and the Chronic Sinusitis Survey (CSS). OBJECTIVE: Develop an Arabic-validated version of both instruments, thus allowing its use among the Arabic population. DESIGN: Prospective cross-sectional study for instrument validation. SETTING: Tertiary university hospital. SUBJECTS AND METHODS: This study was conducted between September 2015 and October 2016. We followed the international comprehensive guidelines for translation and cross-cultural adaptation of QoL instruments. MAIN OUTCOME MEASURES: Test-retest reliability, discriminant validity, and responsiveness ability of both the RSDI and CSS Arabic versions. SAMPLE SIZE: 124. RESULTS: The sample comprised 75 patients diagnosed with chronic rhinosinusitis and 49 healthy control subjects. The Arabic version of both instruments showed high internal consistency (Cronbach’s alpha: RSDI=0.97, CSS=.88) and the ability to differentiate between diseased and healthy volunteers (P<.0001). The translated versions also detected significant change in response to an intervention (P<.0001). CONCLUSION: These Arabic validated versions of the RSDI and CSS can be used for both clinical and research purposes. LIMITATIONS: This study was performed in only one tertiary hospital.